(untitled) (Journal of Oriental Studies, 2019)
In the post-Soviet countries is half a million Korean diaspora, which due to historical events in the late 20th century proved within various territorially-State boundaries. If the first and second generation Koreans had to build ethnic economy theory based flaws and the theory of the enclave, the third and fourth generation ethnic Koreans form the ethnic entrepreneurship according to the theory of social capital to ethnic economy. Based on academic studies data, as well as qualitative analysis of Web sites, the author argues that for a new generation of businessmen KoreSaram ethnic entrepreneurship is based on “the development of a new product or services through innovation and internationalization of ethnic business”. The author suggests that in the absence of ethnic dislocation, as well as in the context of globalization and interna- tionalization, a new generation of Koreans, keeping the traditions of the ethnic economy demonstrates the pattern of ethnic business by building social networks, based on the characteristics of human capital. In addition, this form of business conduct helps maintain ethnic solidarity and preserve the traditional culture of Koreans.